Bridging surgical gaps in congenital heart disease: results from 50 remote telementored procedures using a new national digital platform in Brazil - Monteiro, Rosangela; Rabello, Guilherme; Meneghini, Bianca; Guido, Maria Carolina; Caneo, Luiz Fernando; Tanamati, Carla; Massoti, Maria Raquel; Miana, Leonardo; Morales, Marcelo Marcos; Sgarbieri, Ricardo; Magalhães, Daniel; Arruda, Tamara Menezes; et al. (Frontiers in Cardiovascular Medicine, 2026)
ObjectiveDespite advances in cardiovascular surgery, access to specialized care remains limited in low-resource regions. Telemedicine, which expanded significantly during the COVID-19 pandemic, offers a strategy to mitigate these disparities. The National Teleconference Platform (TAC) was developed to provide real-time, multidisciplinary telementoring for pediatric congenital heart surgery in remote areas.MethodsThis prospective, multicenter study assessed the feasibility, usability, and effectiveness of the TAC platform. The system integrated videoconferencing with Internet of Things (IoT) technologies, enabling synchronous audiovisual communication, real-time monitoring of surgical equipment, and interactive mentorship. Three Brazilian centers from the North, Northeast, and Southeast regions participated. Telementoring encompassed the entire surgical workflow, from anesthesia induction to postoperative debriefing, with data security compliant with national and international standards.ResultsBetween November 2022 and March 2025, 50 pediatric cardiac procedures were performed with complete telementoring in 93% of cases, and no technical failures occurred. Each operating room incorporated seven connected devices. User evaluations revealed high satisfaction: 76% of surgical teams reported increased confidence, 92% preserved autonomy throughout procedures, and all participants highlighted the substantial educational value of the platform.ConclusionThe TAC platform is feasible, effective, and well-accepted for providing multidisciplinary surgical guidance. It optimizes procedural performance, enhances surgical care, and demonstrates significant potential to expand access to specialized healthcare in resource-limited settings.